Selection of drilling fluid system for wells with high CO2 content in Song Hong basin - Huu Hai Ngo; Trong Tai Nguyen; The Vinh Nguyen; Van Tu Truong (Petrovietnam Journal, 2022)
The selection of drilling fluid systems for wells to be drilled plays a vital role in designing and operations, especially for wells that penetrate through challenging geological conditions or through reservoirs containing sour gas. For reservoirs with high CO2 content, during the drilling operations, CO2 gas from the reservoir will influx into the well which causes chemical reactions between CO2 and chemicals used in the mud systems, leading to changes of their properties such as density, viscosity and rheology. These changes lead to incorrect drilling parameters, which can cause problems during operations.The article proposes an option to select a suitable drilling fluid system for wells with high CO2 content in the Song Hong basin in order to reduce risks and improve the efficiency of drilling operations.